DISTORÇÃO IDADE/SÉRIE E SUAS IMPLICAÇÕES NO ENSINO E APRENDIZAGEM: um estudo na turma do 5º ano tarde da Escola Lindalva Pinho Curralinho-PA - NOGUEIRA, Lindalva dos Santos (2024)
This course conclusion work aims to analyze or teach how to distort age / grade, as well as its historical process and its implications in the teaching and learning process. The study was carried out based on a documentary and bibliographic research that will be presented in the theoretical basis. It addresses important aspects such as history of school education, such as theories of learning by Piaget, Vigotsky and Wallon, Relating these theories to school pedagogical practices through documentary and bibliographic research of studies on subject studies. The results corroborate with the literature, which is a problem of great complexity, which starts from a biopsychosocial issue that enters the government, such as laws, policies, educational institution, pedagogical practices, family and also the student. Education is the responsibility of everyone involved. In this way, the student will have the possibility to succeed in his learning process and consequently the progressive advance in his schooling.